Root anatomical traits determined leaf-level physiology and responses to precipitation change of herbaceous species in a temperate steppe - Zhou, Meng; Bai, Wenming; Li, Qingmei; Guo, Yumeng; Zhang, Wen-Hao (The New phytologist, 2021)
• Root anatomy plays important roles in the control of leaf water relations. However, few studies have evaluated whether and how anatomical traits of absorptive roots influence leaf physiology of herbaceous species in a temperate grassland. • We measured absorptive root anatomical traits and leaf physiological traits of 15 herbaceous species in a temperate steppe and monitored their responses to increased precipitation in a field stimulating experiment. • Root anatomical and leaf physiological traits differed among monocotyledonous grasses, monocotyledonous liliaceous species and dicotyledonous forbs. The species with higher stele: root diameter, lower root diameter and cortex thickness exhibited higher transpiration rates and stomatal conductance, but lower intrinsic water-use efficiency. Increased precipitation enhanced transpiration and stomatal conductance of forbs and lilies, but it enhanced photosynthesis in lilies exclusively. The sensitive response of lilies to precipitation may be related to their large root diameter and cortex thickness. • In summary, we observed distinct differences in anatomical traits of absorptive roots among plant groups in temperate steppes. These differences drove variations in leaf physiological traits and their diverse responses to precipitation change. These findings highlight the important roles of root anatomical traits in driving leaf-level physiological processes in temperate grasslands.